Novel spirooxindole compounds as anticancer agents: targeting Plk4 kinase through design, synthesis, and molecular docking - Mervat S. Sammor; Almeqdad Y. Habashneh; Mahmoud A. Al-Sha'er; Sanaa K. Bardaweel; Mustafa M. El‐Abadelah (Pharmacia)
Plk4 plays a crucial role in controlling the duplication of centrioles and initiating the creation of centrosomes. Disruption of Plk4 leads to aneuploidy and chromosome instability, contributing to aggressive cancers, as well as microcephaly and fatal ciliopathies in children. To effectively treat cancer, it is essential to develop potent Plk4 kinase inhibitors, which are promising anticancer agents due to their ability to induce cancer cell death and selectively target centrosome amplification. This paper examines the molecular design tools and efficient synthesis of novel spirooxindole compounds with anticancer properties, potentially mediated by Plk4 kinase suppression and consequent centrosome reduction. A potential anticancer mechanism was investigated by docking the most effective spirooxindoles into the Plk4 kinase ATPase binding site (PDB code: 4JXF, resolution: 2.40 Å). Compounds 4b and 4i showed the highest inhibition against the Caco2 and HCT116 cell lines, with IC₅₀ values of 68 and 63 µM and 55 and 51 µM, respectively. Their LibDock scores were 110.12 and 109.1, suggesting that their anticancer activity may result from Plk4 enzyme inhibition. Notably, these compounds exhibited a high safety margin, with fibroblast cell line inhibition above 1000 µM. In conclusion, these findings support the potential of spirooxindole derivatives as selective and safe Plk4 inhibitors, offering a promising avenue for targeted cancer therapy with minimal toxicity to normal cells. Graphical abstract: